Optimization of Cultural Conditions for Solid State Fermentation of Amylase Production by Aspergillus species - Gautam, Bina; Karki, Tika B; Panta, Om Prakash (Nepal Journal of Science and Technology, 2013)
Amylase is an amylolytic enzyme used in food industry which is generally produced by Aspergillus spp. under solid state fermentation. The present study is concerned with the isolation, screening and selection of suitable strains of Aspergillus spp. and optimization of cultural conditions for the biosynthesis of amylase. Rice and wheat brans were used as substrates which are readily available inexpensive raw materials for amylase production. From 85 samples of rice and wheat grains, 55 colonies obtained on potato dextrose agar (PDA) were suspected to be Aspergillus oryzae and only 35 colonies possessed the morphological characteristics similar to that of A. oryzae indicating the isolates were most likely the strains of A. oryzae. Of all the fungal isolates of Aspergillus spps., Asp.31 gave maximum production of amylase (720.782 IUgds-1) in solid state fermentation media. This strain was selected as a parental strain for optimization for cultural conditions. The obtained data were analyzed using SPSS- 11.5 program. Of all the substrates (rice bran, wheat bran and their mixture), rice bran was the best for producing amylase of highest activity 611.614 IUgds-1.The highest enzyme activity of 698.749 IUgds-1 was observed at 50% initial moisture level of the substrate. The optimum temperature was 25°C for producing the crude amylase enzyme with amylase activity of 577.757 IUgds-1. Nepal Journal of Science and Technology Vol. 14, No. 1 (2013) 67-74 DOI: http://dx.doi.org/10.3126/njst.v14i1.8924